Land Rights in the Land Law System in Indonesia According to the Basic Agrarian Law Number 5 of 1960 - Ni Ketut Suartining; Benny Djaja (Journal of Social Research, 2023)
Law No. 5 of 1960. This law explains that land law in Indonesia is Unofficial. This means that all issues, status, and legal basis of land in Indonesia must refer to UUPA No. 5 of 1960. Actually, this UUPA is a land nationalization project in Indonesia. So that land is properly owned and enjoyed by Indonesian citizens so that foreign nationals do not have the right to land in Indonesia except Hak Pakai. This control is not meant to be Hak Milik, but the state controls land in the sense that the State is given the right to manage land in Indonesia for the prosperity of the Indonesian people themselves. There is recognition of customary law rights, especially in the land sector which is famous for the existence of Customary Rights. The UUPA itself provides recognition of Customary Land Rights. The concept of customary rights is in line with Article 6 of the UUPA that land must have a social function. This means that the function of land is not only for personal interests, but more importantly for the benefit of the wider community or for the common good. Individual rights to land also receive recognition from the UUPA such as Hak Milik (HM), Hak Guna Usaha (HGU), Hak Guna Bangunan (HGB), Hak Pakai (HP), Waqf and Land Security Rights. So it is clear that the Indonesian land law system is indeed based on the noble values of the Indonesian nation itself such as togetherness, justice, prosperity and kinship in land control and utilization while adhering to the principle that land must have a social function.